Philosophical Values Contained in the Sedekah Paret Tradision in the Villange of Terusan Dalam, Sumber Marga District, Telang, Banyuasin Regency - Heryati Heryati; Apriana Apriana; Yusinta Tia Rusdiana; Joko Joko (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
This study aims to analyze the historical background of the Sedekah Parit tradition, describe its implementation process, and examine the philosophical values embodied in the tradition in Terusan Dalam Village, Sumber Marga Telang District, Banyuasin Regency. This research employed a qualitative descriptive approach using the historical method, which consisted of heuristics, source criticism, interpretation, and historiography. Data were collected through observation, interviews, and documentation, while data analysis followed the qualitative analysis model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings reveal that the Sedekah Parit tradition originated from the community’s belief in supernatural forces and gradually transformed with the spread of Islam into a tradition centered on expressing gratitude to Allah SWT. The implementation of the tradition consists of five stages: cleaning the irrigation canals, slaughtering a black native chicken, preparing nasi uduk (coconut rice), reciting Surah Yasin and offering collective prayers, and concluding with a communal feast. The tradition embodies several philosophical values, including religious values, social values, cultural values, mutual cooperation, and local wisdom. These values strengthen social solidarity, preserve local cultural heritage, and maintain harmonious relationships among humans, nature, and God. This study contributes to the advancement of local history, cultural anthropology, and the preservation of Indonesia’s intangible cultural heritage.